Case report: Clinical features and prognosis of two Infants with rhabdomyosarcoma of the tongue - Yang, Peiyi; Xu, Na; Su, Yan; Duan, Chao; Wang, Shengcai; Fu, Libing; Yu, Tong; Guo, Ruolan; Ma, Xiaoli (Frontiers in Oncology, 2023)
Background: Rhabdomyosarcoma (RMS) is the most common soft tissue tumor in children, and its most common pathological types include embryonal RMS and alveolar RMS. In contrast, spindle cell RMS (SRMS) is a rare type. Moreover, the tongue is a rare primary site of RMS, and infancy is a rare age at onset. Case presentation: Two infants were diagnosed with lingual RMS at 3 and 5 months after birth, respectively, and were admitted to Beijing Children's Hospital. The pathological type for both cases was SRMS. Both were classified as low risk and were treated with surgery and chemotherapy. Case 1 was in complete remission at the latest follow up, and Case 2 had a relapse 10 months after stopping chemotherapy, achieving complete remission after the multimodality treatment of chemotherapy, surgery, and radiotherapy. The venous blood gene test of the two infants did not indicate pathogenic mutation or possible pathogenic mutation related to RMS. In Case 1, variants of the CDK4 and BRCA1 genes, both with unknown significance and a possible relation with RMS, were detected. In Case 2, three gene variants of unknown significance that were possibly associated with RMS—TRIP13, APC, and RAD54L—were identified. Conclusion: Lingual RMS in infants is rare. Its clinical manifestations lack specificity, and early recognition is complex. The success and timing of local treatment are important prognostic factors. Genetic testing may be helpful for the early detection of tumor susceptibility and estimation of prognosis.